A study on consumer adoption, intention, product and service innovation leading to consumer loyalty of online food delivery platforms in the development of the post COVID-19 pandemic setup in the Philippines - Laurian, Jana Cassandra Torres (Animo Repository, 2022)
The Online Food Delivery industry is fast growing in the Philippines especially with its rapid growing demand brought by the COVID-19 pandemic. The researchers of this thesis then aim to understand the relationship between the independent variables which are Consumer Adoption, Consumer Intention, Product and Service Innovation to Customer satisfaction on Online Food Delivery platforms and furthermore focus on getting data to help businesses adapt to the post pandemic set-up in terms of retaining customer loyalty on Online Food Delivery platforms. With the utilization of the ordinal logistic regression model, the results presented that there is a significant relationship between customer adoption, customer intention, product and service innovation to customer satisfaction, which then supports the researcher’s hypothesis that these three factors have a significant effect on customer satisfaction. In addition, using a binary logistic model, there is also a positive relationship between customer satisfaction and customer loyalty, which then supports the researcher’s hypothesis that the two aforementioned factors have a significant effect on each other. It was founded in this research that customer adoption, customer intention, product and service innovations all lead to customer satisfaction which then leads to customer loyalty, which implies that online food delivery platforms have a huge potential and is the future major outlet of the food industry.